2020
DOI: 10.1371/journal.pone.0237455
|View full text |Cite
|
Sign up to set email alerts
|

De novo sequence assembly requires bioinformatic checking of chimeric sequences

Abstract: De novo assembly of sequence reads from next generation sequencing platforms is a common strategy for detecting presence and sequencing of viruses in biospecimens. Amplification artifacts and presence of several related viruses in the same specimen can lead to assembly of erroneous, chimeric sequences. We now report that such chimeras can also occur between viral and non-viral biological sequences incorrectly joined together which may cause erroneous detection of viruses, highlighting the importance of perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Phenotypically, E. coli 125 was susceptible to penicillin ( Avershina et al, 2021b ), which suggests that the TEM-1B gene in this isolate was not expressed. Due to numerous rounds of PCR, Illumina sequencing data are prone to chimera generation ( Arroyo Mühr et al, 2020 ), and chimera removal is a common filtering step when using amplicon sequencing with Illumina ( Prodan et al, 2020 ). However, it seems doubtful that a TEM-1B-identical sequence would be chimera-generated.…”
Section: Discussionmentioning
confidence: 99%
“…Phenotypically, E. coli 125 was susceptible to penicillin ( Avershina et al, 2021b ), which suggests that the TEM-1B gene in this isolate was not expressed. Due to numerous rounds of PCR, Illumina sequencing data are prone to chimera generation ( Arroyo Mühr et al, 2020 ), and chimera removal is a common filtering step when using amplicon sequencing with Illumina ( Prodan et al, 2020 ). However, it seems doubtful that a TEM-1B-identical sequence would be chimera-generated.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent post assembly assessment is mandatory to reduce the risk of chimeric sequences and possible miscalling of HPV positivity in samples and/or erroneous calling of new HPV variants/genotypes. HPV-Chimera scripts exist to help researchers determine the accuracy of their HPV contigs [ 12 , 77 ].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in recent years, various studies have utilized NGS approaches to generate detailed insights into potential disease-related mechanisms of HPV. NGS has shown that certain sublineages of HPV are associated with a higher risk of cancer [ 9 , 10 , 11 ], and its high sensitivity also allows the attributable fraction of cervical cancer associated with HPV to be determined with greater precision compared to traditional PCR techniques [ 12 , 13 ]. Further, NGS has identified certain single-nucleotide polymorphisms (SNPs) associated with a higher likelihood of viral persistence [ 14 ] and the key role of HPV E7 gene conservation in cervical cancer development [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter occurring during library preparation [6,7], or during the de novo assembly process [8,9], where there is a requirement to traverse paths across graphs constructed from read data that ranges in complexity depending on the nature of the gene families being represented [10][11][12]. Chimeras also occur at a genomic level during de novo assembly, such as when inferring haplotypes [13,14], but the causes, and consequences, at a genomic level are different [15][16][17]. In genomic assembly the aim is to reconstruct fewer large contigs that represent chromosomes [18,19].…”
Section: Introductionmentioning
confidence: 99%